THE RELEVANCE OF AGENCY THEORY IN THE DYNAMICS OF MANAGER-INVESTOR RELATIONSHIPS IN THE DIGITAL ERA - Anurak Chaiyasit (Count : Journal of Accounting, Business and Management, 2025)
This study aims to explore the relevance of classical agency theory in the context of digital transformation, specifically focusing on the evolving relationship between managers and investors. As financial reporting and corporate governance shift toward digital platforms—incorporating tools such as real-time disclosures, blockchain, and AI—this research investigates whether these technologies mitigate or reshape agency conflicts. A quantitative method was employed through an online survey of 120 respondents, including corporate managers and institutional investors in Indonesia. The results show that digital tools significantly enhance managerial transparency and investor trust; however, they also introduce new complexities such as algorithmic opacity, information overload, and challenges in accountability. Notably, the study reveals that investor trust in digital environments is highly dependent on information usability, not merely availability. The research contributes novel insights by proposing a theoretical extension of agency theory that incorporates digital governance variables and behavioral trust mechanisms. This is particularly important in emerging markets, where digital maturity and regulatory structures vary widely. Furthermore, the study highlights a critical paradox in digital transparency: more data does not always lead to better governance outcomes. In conclusion, this research offers both theoretical advancement and practical guidance for aligning digital tools with effective corporate oversight. It also serves as a foundation for future studies to develop hybrid governance models that integrate technological innovation with classical agency perspectives.